Comparative proteomic analysis of the ATP‐sensitive K+ channel complex in different tissue types. Issue 2 (3rd January 2013) - Kefaloyianni, Eirini; Lyssand, John S.; Moreno, Cesar; Delaroche, Diane; Hong, Miyoun; Fenyö, David; Mobbs, Charles V.; Neubert, Thomas A.; Coetzee, William A.; Wu, Fang‐Xiang; Ressom, Habtom; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> ATP‐sensitive K+ (KATP) channels are expressed ubiquitously, but have diverse roles in various organs and cells. Their diversity can partly be explained by distinct tissue‐specific compositions of four copies of the pore‐forming inward rectifier potassium channel subunits (Kir6.1 and/or Kir6.2) and four regulatory sulfonylurea receptor subunits (SUR1 and/or SUR2). Channel function and/or subcellular localization also can be modified by the proteins with which they transiently or permanently interact to generate even more diversity. We performed a quantitative proteomic analysis of KATP channel complexes in the heart, endothelium, insulin‐secreting min6 cells (pancreatic β‐cell like), and the hypothalamus to identify proteins with which they interact in different tissues. Glycolysis is an overrepresented pathway in identified proteins of the heart, min6 cells, and the endothelium. Proteins with other energy metabolic functions were identified in the hypothalamic samples. These data suggest that the metabolo‐electrical coupling conferred by KATP channels is conferred partly by proteins with which they interact. A large number of identified cytoskeletal and trafficking proteins suggests endocytic recycling may help control KATP channel surface density and/or subcellular localization. Overall, our data demonstrate that KATP channels in different tissues may assemble with proteins having common functions, but that tissue‐specific complex organization also occurs.